2013
DOI: 10.1002/dta.1456
|View full text |Cite
|
Sign up to set email alerts
|

UR‐144 in products sold via the Internet: Identification of related compounds and characterization of pyrolysis products

Abstract: The synthetic cannabinoid, UR-144 ((1-pentyl-1H-indol-3-yl)(2,2,3,3-tetramethylcyclopropyl)methanone), was identified in commercial 'legal high' products (herbal, resin, and powder). Along with this, six related compounds were detected. The most abundant one (2.1) was identified as 4-hydroxy-3,3,4-trimethyl-1-(1-pentyl-1H-indol-3-yl)pentan-1-one, a product of the electrophilic addition of water to the cyclopropane moiety in UR-144. Compound 2.1 was found to be undergo cyclisation which leads to the formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 38 publications
(48 reference statements)
5
38
0
2
Order By: Relevance
“…UR-144 pyrolyzed almost completely into a single component under these conditions. NMR analysis indicated that the obtained compound was identical to a UR-144 degradant in which the cyclopropyl ring was opened, as reported previously ( Kavanagh et al, 2013) (Table 1). Therefore, the pyrolyzed UR-144 was used in the following experiments as the UR-144 degradant.…”
Section: Smoke Of Ur-144 Herb Contains Ur-144 and Ur-144 Degradantsupporting
confidence: 84%
“…UR-144 pyrolyzed almost completely into a single component under these conditions. NMR analysis indicated that the obtained compound was identical to a UR-144 degradant in which the cyclopropyl ring was opened, as reported previously ( Kavanagh et al, 2013) (Table 1). Therefore, the pyrolyzed UR-144 was used in the following experiments as the UR-144 degradant.…”
Section: Smoke Of Ur-144 Herb Contains Ur-144 and Ur-144 Degradantsupporting
confidence: 84%
“…Second, the cyclopropyl ring is under strain and has been shown to be unstable under certain conditions. Shevyrin et al (18) and Kavanagh et al (24) proposed ring opening during 2,2,3,3-TMCP cannabinoid stability studies. The cyclopropyl ring can be cleaved when heated, forming isomers carrying a pent-4-en-1-one chain.…”
Section: Discussionmentioning
confidence: 99%
“…This compound caused positive effects in single cell gel electrophoresis assays (SCGE) with human derived cells (Koller et al, 2013). UR-144 was detected in many European countries, Japan and in the US (Choi et al, 2013) (Kavanagh et al, 2013;Uchiyama et al, 2013). Furthermore, we investigated in the present study two alkylindazoles.…”
Section: Introductionmentioning
confidence: 91%